1996
DOI: 10.1212/wnl.47.4.1021
|View full text |Cite
|
Sign up to set email alerts
|

The amygdala and intractable temporal lobe epilepsy

Abstract: The combination of AT2 mapping and FLAIR is a sensitive method to detect lesions that are not seen on routine MRI in the amygdalae of patients with intractable TLE. Further correlational studies will be required to define the role of this technique in the presurgical evaluation of patients with intractable TLE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
62
1
2

Year Published

1997
1997
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 100 publications
(70 citation statements)
references
References 82 publications
5
62
1
2
Order By: Relevance
“…In patients with HS, the amygdala may be affected by the same sclerotic pathology as the hippocampus, although the severity of hippocampal and amygdala sclerosis in a given patient may be uncorrelated (Hudson et al, 1993). As in the case of the hippocampus, amygdala pathology may be assessed using MRI by measuring T2 signal (Van Paesschen et al, 1996;Bartlett et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…In patients with HS, the amygdala may be affected by the same sclerotic pathology as the hippocampus, although the severity of hippocampal and amygdala sclerosis in a given patient may be uncorrelated (Hudson et al, 1993). As in the case of the hippocampus, amygdala pathology may be assessed using MRI by measuring T2 signal (Van Paesschen et al, 1996;Bartlett et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…We did not observe any high signal in the amygdala whilst Bergin et al [11]reported 5 patients with high signals located in that structure. High signals visible in the amygdala on fast FLAIR sequences have recently been described by Van Paesschen et al [20]. In our study, none was reported probably because these lesions were detected on conventional MRI and the corresponding patients would subsequently have been excluded from this study.…”
Section: Discussionmentioning
confidence: 49%
“…T 2 -mapping of the amygdala (AT2) has therefore been applied in patients with epilepsy (Kalviainen et al, 1997a). The principle is similar to HCT2 mapping, but the orientation is a tilted axial plane, allowing the evaluation of the amygdala independently of the hippocampus (Van Paesschen et al, 1996). In a study of patients with TLE, abnormal AT2 ipsilateral to the seizure focus was seen in 52 % of patients.…”
Section: Epilepsymentioning
confidence: 99%